Scriptures To Pictures: Interrogating The Channels of Adapting Bible Stories for Contemporary Audiences (Integral Research, 2024)
Effective communication in today's contemporary world is a herculean task as audiences have transitioned beyond the traditional means of accepting information through verbal and non-verbal communication to the level of aesthetic communication. The bible for one, is a phenomenal religious book that contains sacred truths and deep meanings capable of yielding its readers to repentance and salvation. However, contemporary society has become excessively familiar with the wordings of the scriptures, and they hardly generate new meaning or understanding from the written words or spoken texts. For some others, the scripture is a compilation of esoteric messages that must be expounded into simpler contexts. Hence, in the similitude of the medieval era, dramatists have sought to dramatize the scriptures into pictures and audio-visuals using the channels of adaptation to aesthetically present the gospel message without watering down its essence and sacred meaning to ensure effective communication and understanding of the scriptures. This study engages Ole Thyssen’s theory of aesthetic communication as a theoretical framework which identifies aesthetics as a quintessential factor in communication with contemporary audiences. It explores the channels of adapting scriptures for today's audiences. Thus, the study recommends that aesthetics should be prioritized for biblical messages to be communicated effectively to contemporary audiences. Hence, it proposes adapting biblical stories into cultural contexts or theatrical modernization to fit into the culture or mindset of the receiving audience and enhance interpretation.
Keywords: Adaptation, Aesthetics, Audiences, Biblical Dramatization, Communication, Contemporary Theatre, Scriptures.